2022
DOI: 10.1108/jima-12-2021-0400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knowledge, social and religious factors effecting the intention of Muslims in Pakistan to receive COVID-19 vaccination: mediating role of attitude towards COVID-19 vaccination

Abstract: Purpose This study aims to empirically examine the knowledge, social and religious factors effecting the intention to receive COVID-19 vaccination while considering the mediating role of attitude towards COVID-19 vaccination. The research explores how the Islamic ideologies shape Muslims’ knowledge, social and religious beliefs towards COVID-19 vaccination acceptance or refusal. Design/methodology/approach Theoretically, the study is based on the functional theory of attitudes. The model of the study is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
(109 reference statements)
0
3
1
Order By: Relevance
“…In this study, conducted with Muslims living in Turkey, the vaccinated group was more religious than the unvaccinated group. In contrast to our study, the study conducted with Muslims living in Pakistan reported that religiosity negatively influenced attitudes toward COVID-19 vaccination [35]. A meta-analysis examining the impact of religiosity on COVID-19 vaccination rates reported that Christianity was negatively associated with vaccination and had no association with Islam, Buddhism, Hinduism, and non-belief [36].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, conducted with Muslims living in Turkey, the vaccinated group was more religious than the unvaccinated group. In contrast to our study, the study conducted with Muslims living in Pakistan reported that religiosity negatively influenced attitudes toward COVID-19 vaccination [35]. A meta-analysis examining the impact of religiosity on COVID-19 vaccination rates reported that Christianity was negatively associated with vaccination and had no association with Islam, Buddhism, Hinduism, and non-belief [36].…”
Section: Discussioncontrasting
confidence: 99%
“…The Islamic explanation for the existence of infectious diseases, Islam through its broad and universal teaching tools quite firmly and clearly also provides an explanation of how to take countermeasures when in a situation of dealing with a virus or epidemic . (Aziz, Niazi & Ghani, 2022). In this context, the Islamic perspective is more likely to talk about handling epidemics at the macro level, simply providing confirmation of the argument that efforts to mitigate pandemics or epidemics have a very strong and firm theological basis, both textually and historically.…”
Section: Handling the Pandemic In Islammentioning
confidence: 92%
“…It has existed for a long time and was mentioned, even long before the emergence of the Covid-19 situation. There are many explanations related to the outbreak of infectious diseases of the country's Covid-19, in the form of religious texts from the Qur'an and hadiths as well as explanations from historical sources such as the incidence of infectious epidemics in the past (Aziz, Niazi & Ghani, 2022). While at the same time provided the countermeasures when in a situation of dealing with a virus or epidemic .…”
Section: Introductionmentioning
confidence: 99%
“…In their study of the willingness of health care workers to take the COVID-19 vaccination, Kumar et al (2021) uncovered wide-ranging justifications for vaccine hesitance, including vaccine safety concerns, anti-vaccination persuasions, personal choice, and waiting until others took the vaccine. Religious belief and various forms of religiosity can shape people's attitudes toward their health and COVID-19 vaccines specifically (Aziz, Niazi, & Ghani 2022;Ng et al, 2022;Salam, 2021). Corcoran, Scheitle, and DiGregorio (2021) identify Christian nationalism as one of the leading predictors of COVID-19 vaccine hesitancy.…”
Section: Literature Review: Attitudes Toward Covid 19 Vaccinesmentioning
confidence: 99%